The Role Of Parents To Increase Children's Interest In Learning In Farmer Families At Gunung Sari Village Alok District Sikka Regency - Febrianti, Nadia; Yanto Yanto; Nur Syamsiyah Ekhsan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Parents are the main person in charge of their child's education. Wherever children go to school, whether in formal, informal or non-formal institutions, parents still play a role in determining the future of their children's education. Therefore, the objective of research is to describe problems and to know roles of parents in increasing children’s interest in learning in farmer families at gunung Sari Village, Alok District, Sikka Regency. This research is a qualitative descriptive which took place in Gunung Sari Village, Alok District, Sikka Regency. The data sources used primary and secondary data sources. The techniques used in data collection are observation and interviews. The data analysis technique used data reduction, data display and conclusion drawing. The result of research showed that there were problems faced by patents such as lazy children in terms of learning and also children spending more time playing. Then 2 parents found difficulties in children’s learning such as the existence of conflicting responses in the child so that the learning outcomes achieved were lowern their potential. Meanwhile, the roles of parents showed that parents as Educator, motivator, facilitator and mentor.